Women as Gleaned in Samantapāsādikā and Divyāvadāna: A Comparative Study (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The changing norms of society in ancient India leading to the change in the status of women played an important role in the increasing involvement of woman in Buddhism.The Buddhist texts not only tell us about the status of those women who adopted Buddhism but also about the women in society at large during the period of their composition.The present paper  is about a comparative study of the treatement of women of the time when the two texts were composed.We find some differences between status of women in both the texts. Through the study we are also able to compare between the woman of the high and low classes.